2020
DOI: 10.3390/cells9040889
|View full text |Cite
|
Sign up to set email alerts
|

Proton Irradiation Increases the Necessity for Homologous Recombination Repair Along with the Indispensability of Non-Homologous End Joining

Abstract: Technical improvements in clinical radiotherapy for maximizing cytotoxicity to the tumor while limiting negative impact on co-irradiated healthy tissues include the increasing use of particle therapy (e.g., proton therapy) worldwide. Yet potential differences in the biology of DNA damage induction and repair between irradiation with X-ray photons and protons remain elusive. We compared the differences in DNA double strand break (DSB) repair and survival of cells compromised in non-homologous end joining (NHEJ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 76 publications
2
41
0
Order By: Relevance
“…Comparing the distribution of γH2AX foci after 3 Gy of photon and proton irradiation, it was reported that photon irradiation resulted in the formation of small γH2AX foci that were equally distributed within the nucleus. Proton irradiation in the SOBP composed of 6 Bragg peaks of 100–110 MeV, on the other hand, induced the formation of larger γH2AX foci that were more heterogeneously distributed within the nucleus [ 67 ]. Multiple other studies have also observed larger γH2AX foci after proton compared to photon irradiation, which could be due to the clustered nature of the DNA damage induced by proton radiation [ 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: The Dna Damage Response After Proton Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the distribution of γH2AX foci after 3 Gy of photon and proton irradiation, it was reported that photon irradiation resulted in the formation of small γH2AX foci that were equally distributed within the nucleus. Proton irradiation in the SOBP composed of 6 Bragg peaks of 100–110 MeV, on the other hand, induced the formation of larger γH2AX foci that were more heterogeneously distributed within the nucleus [ 67 ]. Multiple other studies have also observed larger γH2AX foci after proton compared to photon irradiation, which could be due to the clustered nature of the DNA damage induced by proton radiation [ 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: The Dna Damage Response After Proton Radiationmentioning
confidence: 99%
“…Multiple other studies have also observed larger γH2AX foci after proton compared to photon irradiation, which could be due to the clustered nature of the DNA damage induced by proton radiation [ 68 , 69 , 70 , 71 , 72 , 73 ]. In addition, slower repair kinetics after proton therapy have been observed [ 30 , 67 , 71 , 73 , 74 , 75 , 76 ]. This is indicative of clustered DNA damage, which is thought to result in slower repair [ 77 ].…”
Section: The Dna Damage Response After Proton Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the suggested higher relative importance of HRR for the repair of DNA damage induced by particle therapy (e.g. carbon ions [49], and proton beam therapy [50][51][52][53]) may even offer potential future opportunities for the stratification of patients with oncometabolite-rich tumors towards particle therapy, or combining particle therapy approaches with metabolic drugs inducing HRR defects during therapy.…”
Section: Therapeutic Strategies Using Synthetic Lethality With Genetimentioning
confidence: 99%
“…Recently, Szymonowicz et al compared BRCA2-proficient BxPC3 and Capan-1 pancreatic cancer cells with BRCA2-deficiency, and showed that both cell lines were more sensitive to proton than to photon irradiation. The sensitising effect was even more noticeable in Capan-1 cells, leading the authors to suggest a predominant role of HR in the repair of clustered DNA damage induced by protons [ 142 ]. This was also demonstrated in lung cancer and glioblastoma cell lines where the impairment of HR led to a higher sensitisation after proton irradiation compared to photons for which the effect of NHEJ pathway inhibition was more pronounced [ 143 ].…”
Section: Pushing Forward Loco-regional Control: Modern Rtmentioning
confidence: 99%